Selection and characterization of a mutant of feline immunodeficiency virus resistant to 2',3'-dideoxycytidine. - Medlin, H K (1996)
We have selected and plaque purified a mutant of feline immunodeficiency virus (FIV) that is resistant to 2',3'-dideoxycytidine (ddC). This mutant was selected in cultured cells in the continuous presence of 25 microM ddC. The mutant, designated DCR-5c, was fourfold resistant to ddC, threefold resistant to 2',3'-dideoxyinosine, and more than fourfold resistant to phosphonoformic acid. DCR-5c displayed little or no resistance to (-)-beta-2',3'-dideoxy-3'-thiacytidine, 3'-azido-3'-deoxythymidine, or 9-(2-phosphonylmethoxyethyl) adenine. Reverse transcriptase purified from DCR-5c was less susceptible to inhibition by ddCTP, phosphonoformic acid, ddATP, or azido-dTTP than the wild-type FIV reverse transcriptase. Sequence analysis of DCR-5c revealed a single base change (G to C at nucleotide 2342) in the reverse transcriptase-encoding region of FIV. This mutation results in substitution of His for Asp at codon 3 of FIV reverse transcriptase. The role of this mutation in ddC resistance was confirmed by site-directed mutagenesis.